Trends In School Enrollment And Graduation: The Experience Of Educational Management Students In The Graduate School - Noemi B. Zulieta; I Ketut Sudarsana; Gilbert S. Arrieta; Inero V. Ancho (Jurnal Penjaminan Mutu, 2020)
The study looked into the trends in the enrollment and graduation of educational management (EdM) students in a teacher education institution in Manila. Considering the challenges of graduate students who are also teachers or supervisors in their respective schools, it may be difficult for them to manage work and studies simultaneously which may lead to dropping from the course or unsuccessfully completing their masters and doctoral studies. Based on the data, it found out that enrollment in the master’s level decreased but is stable in the doctoral level in the last six academic years (2013-2014 to 2018-2019). In particular, there is a significant decrease in summer enrollment in both levels. There were more female than male students who enrolled in the program. In terms of successful completion, the number of graduates is significantly low and more female than male students graduated.